Asymmetric induction in reactions of chiral carboxylic esters and silyl enol ethers - Evans, Melanie Daryl (Rhodes University, Faculty of Science, Department of Chemistry, 1998)
Several camphor and pinane derivatives have been synthesised and evaluated for use as chiral auxiliaries in asymmetric synthesis. Various blocking groups have been attached to the camphor skeleton in attempts to improve stereofacial selectivity; these include Î±-methoxybenzyl and xylyl groups, and novel stereoisomeric ketal moieties derived from meso- and (R,R)-(-)-2,3-butanediol. Benzylation reactions carried out on the lithium enolates of ester derivatives of the camphor-derived chiral auxiliaries afforded Î±-benzylated products in 5-60% diastereomeric excess. Stereochemical aspects have been explored using high resolution NMR, X-ray crystallographic and computer modelling techniques, and hydrolysis of selected Î±-benzylated products has permitted the diasteroselective bias to be confirmed. Opposite configurations at the new stereogenic centre are clearly favoured by the xylyl and ketal blocking groups - an observation rationalised in terms of the presence or absence of chelating potential in the blocking group. Baylis-Hillman reactions carried out on a series of specially prepared camphor-derived acrylic esters containing the ketal blocking group exhibited both low diastereoselectivities (0-30% d.e.) and very long reaction times. Chiral silyl enol ethers, synthesised using both pinane and camphor derivatives as chiral auxiliaries, showed up to 20% diastereomeric excess in MCPBA oxidation, alkylation and Mukaiyama reactions. Attempts to bring the prochiral centre in the silyl enol ether substrates closer to the chiral auxiliary, and thus improve the stereofacial selectivity, proved unsuccessful. The silyl enol ether derivatives, however, display interesting fragmentation patterns in their electron impact mass spectra, which were investigated using a combination of high resolution MS, comparative low resolution MS and metastable peak analysis.
Keywords: Ethers -- Synthesis; Esters -- Synthesis; Chirality; Asymmetric synthesis; Organic compounds -- Synthesis